Low Temperature WGS Catalysts for Hydrogen Station and Fuel Processor Applications - Moon, Dong Ju (SPRINGER/PLENUM PUBLISHERS, 2009)
Generally, water gas shift (WGS) reaction is a very important step in the industrial production of hydrogen, ammonia and other bulk chemicals utilizing synthesis gases. In this paper, we are reporting WGS reaction carried out in our research group for the application of hydrogen station and fuel processor. We prepared various Mo2C, Pt-Ni-based and Cu-based catalysts for low temperature WGS reaction. The characteristics of the prepared catalyst were analyzed by N-2 physisorption, CO chemisorptions, XRD, SEM and TEM technologies, and compared with that of commercial Cu-Zn/Al2O3 catalyst. It was found that prepared catalysts displayed reasonably good activity and thermal cycling stability than commercial LTS (Cu-Zn/Al2O3) catalyst. It was found that the deactivation of commercial LTS catalyst during the thermal cycling run at 250 degrees C was caused by the sintering of active metal even though it shows high activity at less than 250 degrees C. The deactivation of Mo2C catalyst during the thermal cycling run was caused by the transition of Mo delta+, Mo-IV and Mo2C on the surface of Mo2C catalyst to Mo-VI(MoO3) with the reaction of H2O in reactants. However, they showed higher stability than the commercial LTS catalyst during thermal cycling test. The Pt-Ni/CeO2 catalyst after the thermal cycling shows slightly deactivation due to the sintering of Ni metal. Among Cu-based catalysts, it was found that Cu-Mo/Ce0.5Zr0.5O2 catalyst has higher WGS activity and stability over commercial LTS catalyst. The results suggested that Pt-Ni/CeO2 and Cu-Mo/Ce0.5Zr0.5O2 catalysts are desirable candidates for application in hydrogen station and fuel processor system even though all other catalysts deactivated slowly during the thermal cycling run.
Keywords: WATER-GAS SHIFT; PARTIAL OXIDATION; TUNGSTEN CARBIDES; MOLYBDENUM; HYDRODENITROGENATION; REDUCTION; CHEMISTRY; NITRIDES; PT/CEO2; SYNGAS